Rotational inertia interface in a dynamic lattice of flexural beams. (1st May 2017) - Piccolroaz, A.; Movchan, A.B.; Cabras, L.
Abstract: The paper presents a novel analysis of a transmission problem for a network of flexural beams incorporating conventional Euler–Bernoulli beams as well as Rayleigh beams with the enhanced rotational inertia. Although, in the low-frequency regime, these beams have a similar dynamic response, we have demonstrated novel features which occur in the transmission at higher frequencies across the layer of the Rayleigh beams.